2013
DOI: 10.1007/s00262-013-1397-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclophosphamide and IL-2 on regulatory CD4+ T cell frequency and function in melanoma patients vaccinated with HLA-class I peptides: impact on the antigen-specific T cell response

Abstract: The frequency and function of regulatory T cells (Tregs) were studied in stage II–III melanoma patients who were enrolled in a phase II randomized trial of vaccination with HLA-A*0201-modified tumor peptides versus observation. The vaccinated patients received low-dose cyclophosphamide (CTX) and low-dose interleukin-2 (IL-2). Tregs were analyzed in the lymph nodes (LNs) of stage III patients who were undergoing complete lymph node dissection and in peripheral blood mononuclear cells (PBMCs) collected before va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
0
24
2
Order By: Relevance
“…For instance, circulating T reg from melanoma patients showed significantly higher IFN-γ secretion following a protocol of tumor peptide vaccination plus IL-2 and cyclophosphamide, in line with enhanced serum IL-12 (158). On the whole, these data suggest that, especially in the human system, the transition from T-bet + T reg , specialized Th1 suppressors, into T-bet + IFN-γ + T reg , Th1-like plastic cells, may not only depend on the availability and the responsiveness to exogenous stimuli, but may differentially occur in distinct T reg precursors: on the one side, tT reg , enriched in committed and self-specific cells, may be forced to arrest to the specialization (T-bet + ) endpoint; on the other side, pT reg , containing less committed and foreign antigens-specific cells, may be more prone to the complete reprograming into pro-inflammatory (T-bet + IFN-γ + ) cells.…”
Section: Heterogeneity and Plasticity Of Ttreg And Ptregmentioning
confidence: 99%
“…For instance, circulating T reg from melanoma patients showed significantly higher IFN-γ secretion following a protocol of tumor peptide vaccination plus IL-2 and cyclophosphamide, in line with enhanced serum IL-12 (158). On the whole, these data suggest that, especially in the human system, the transition from T-bet + T reg , specialized Th1 suppressors, into T-bet + IFN-γ + T reg , Th1-like plastic cells, may not only depend on the availability and the responsiveness to exogenous stimuli, but may differentially occur in distinct T reg precursors: on the one side, tT reg , enriched in committed and self-specific cells, may be forced to arrest to the specialization (T-bet + ) endpoint; on the other side, pT reg , containing less committed and foreign antigens-specific cells, may be more prone to the complete reprograming into pro-inflammatory (T-bet + IFN-γ + ) cells.…”
Section: Heterogeneity and Plasticity Of Ttreg And Ptregmentioning
confidence: 99%
“…In a randomized phase II trial, administration of a single dose of cyclophosphamide, followed by vaccination 3 days later with IMA901, a vaccine that consists of multiple-tumor associated peptides (TUMAPs) plus granulocyte-macrophage colony-stimulating factor (GM-CSF), reduced the number of Tregs and was associated with prolonged survival in immune responder patients with advanced renal cell cancer [52]. Similarly, peripheral blood mononuclear cells (PBMCs) analysis of stage II-III melanoma patients, who were vaccinated with HLA-A*0201-modified tumor peptides 7 days after low-dose of cyclophosphamide, showed transient reduction in the frequency of Tregs and an increase in vaccine-induced antigen specific CD8 + T-cells [50]. Other studies in which cyclophosphamide treatment was used, showed that the depletion of Tregs may be associated with the induction of Th17, Th1 and vaccine-induced CD25 + CD4 + Foxp3-negative effector T-cells [65,66].…”
Section: Administration Of Chemotherapy Before Vaccination Alleviatesmentioning
confidence: 99%
“…Several studies suggest that the optimal time point for vaccination is 3-7 days after this type of chemotherapy [50][51][52]. In a randomized phase II trial, administration of a single dose of cyclophosphamide, followed by vaccination 3 days later with IMA901, a vaccine that consists of multiple-tumor associated peptides (TUMAPs) plus granulocyte-macrophage colony-stimulating factor (GM-CSF), reduced the number of Tregs and was associated with prolonged survival in immune responder patients with advanced renal cell cancer [52].…”
Section: Administration Of Chemotherapy Before Vaccination Alleviatesmentioning
confidence: 99%
“…A recent adjunct to the plethora of escape mechanisms is the infl ammasome component Nirp3 underlining the complex relationship between infl ammation and cancer [ 27 ] that impairs vaccine-induced immunity. However, one should consider that several mechanisms may be activated by tumor cells either simultaneously or one after the other according to modifi cations that occur in the tumor microenvironment and in different tissues in which tumor cells are growing even during different types of therapy [ 28 ]. A recent additional mechanism of tumor escape has been described that includes tumor cell secretion of sterol metabolites (LXR ligands), which inhibit the expression of CCR7 on the cell surface of dendritic cells (DCs), thereby disrupting DC migration to the lymph nodes and dampening the antitumor immune priming event [ 29 ].…”
Section: Factors That May Impair the Immune Response Against Tumorsmentioning
confidence: 99%